Laser cutting of steel plates up to 100 mm in thickness with a 6-kW fiber laser for application to dismantling of nuclear facilities. (January 2018) - Shin, Jae Sung; Oh, Seong Yong; Park, Hyunmin; Chung, Chin-Man; Seon, Sangwoo; Kim, Taek-Soo; Lee, Lim; Lee, Jonghwan
Highlights: A cutting study with a high power ytterbium-doped fiber laser was conducted for application to dismantling of nuclear facilities. Stainless steel and carbon steel plates of various thicknesses were cut at a laser power of 6-kW. Despite the use of a low output of 6-kW, the cutting was successful for both stainless steel and carbon steel plates up to 100 mm in thickness. The cutting capability was ∼16.7 mm by kW which is much higher than commonly known value, and the maximum cutting speeds were faster for the same thicknesses than those from other groups. Abstract: A cutting study with a high-power ytterbium-doped fiber laser was conducted for the dismantling of nuclear facilities. Stainless steel and carbon steel plates of various thicknesses were cut at a laser power of 6-kW. Despite the use of a low output of 6-kW, the cutting was successful for both stainless steel and carbon steel plates of up to 100 mm in thickness. In addition, the maximum cutting speeds against the thicknesses were obtained to evaluate the cutting performance. As representative results, the maximum cutting speeds for a 60-mm thickness were 72 mm/min for the stainless steel plates and 35 mm/min for the carbon steel plates, and those for a 100-mm thickness were 7 mm/min for stainless steel and 5 mm/min for carbon steel plates. These results show an efficient cutting capability of about 16.7 mm by kW, whereas other groups have shown cutting capabilities of ∼10 mm by kW. Moreover, the maximum cutting speeds were faster for the same thicknesses than those from other groups. In addition, the kerf widths of 60-mm and 100-mm thick steels were also obtained as another important parameter determining the amount of secondary waste. The front kerf widths were ∼1.0 mm and the rear kerf widths were larger than the front kerf widths but as small as a few millimeters.